BNIP3 Interacting with LC3 Triggers Excessive Mitophagy in Delayed Neuronal Death in Stroke. (17th September 2014) - Shi, Ruo‐Yang; Zhu, Sheng‐Hua; Li, Victor; Gibson, Spencer B.; Xu, Xing‐Shun; Kong, Ji‐Ming
Summary Introduction A basal level of mitophagy is essential in mitochondrial quality control in physiological conditions, while excessive mitophagy contributes to cell death in a number of diseases including ischemic stroke. Signals regulating this process remain unknown. BNIP3, a pro‐apoptotic BH3‐only protein, has been implicated as a regulator of mitophagy. Aims Both in vivo and in vitro models of stroke, as well as BNIP3 wild‐type and knock out mice were used in this study. Results We show that BNIP3 and its homologue BNIP3L (NIX) are highly expressed in a "delayed" manner and contribute to delayed neuronal loss following stroke. Deficiency in BNIP3 significantly decreases both neuronal mitophagy and apoptosis but increases nonselective autophagy following ischemic/hypoxic insults. The mitochondria‐localized BNIP3 interacts with the autophagosome‐localized LC3, suggesting that BNIP3, similar to NIX, functions as a LC3‐binding receptor on mitochondria. Although NIX expression is upregulated when BNIP3 is silenced, up‐regulation of NIX cannot functionally compensate for the loss of BNIP3 in activating excessive mitophagy. Conclusions NIX primarily regulates basal level of mitophagy in physiological conditions, whereas BNIP3 exclusively activates excessive mitophagy leading to cell death.